Bagaço e fécula de mandioca na elaboração de farinhas cruas e pré-gelatinizadas, snacks e macarrões instantâneos com amaranto - FIORDA, Fernanda Assumpção (2011)
Cassava is a starchy tuberous root of great energetic potential, and can be used for both in natura consumption and for industrial processing, which generates significant amounts of ba-gasse that is potentially useful as a source of dietary fiber. Studies have shown the benefits of functional food, and that has led to an increase in consumer interest. Extrusion technology had been used lately for the development of new food products. Pasta has been incorporated as part of Brazilian cuisine, being served as a main course or a side dish, in many different com-binations. Due to the nutritional advantages of the amaranth, much research has been made on the use of its flour as a substitute for wheat flour in cooking with the final goal of a more nu-tritious product. This work focused on evaluating the effect of temperature of extrusion and moisture on the physical and technological properties of extruded products made trough mix-tures of starch and flour from the cassava (70:30) bagasse. Extrusion was made with a single screw extruder and followed the central rotational composite design with two factors or in-dependent variables for mixture moisture and extrusion temperature, on a total of 12 treat-ments. It was also intended to analyze the effect of the components on the boiling properties of pre-boiled pasta made of cassava (70:30) bagasse and pre-gelatinized starch flour, cassava starch and amaranth flour through mixture design, and to assess the physical, technological and nutritional properties of this pasta. The properties of the extruded products that were ana-lyzed were: expansion index, specific volume, water-absorption index, solubility in water index, oil-absorption index, activity of water and color. Analysis of texture and scanning elec-tron microscopy were performed on the pasta. An ideal formulation was set and its centesimal composition and quality parameters determined and compared to commercial pasta of both standard and wholemeal flour. Clear products with high expansion and intermediate specific volume were obtained at intermediate extrusion temperature conditions (104,10 ºC) and mix-ture moisture [16 g (100 g) -1]. Acceptance tests indicated consumers rated it very good (7,2 score) with a 42% purchase intention. The results obtained showed that the combined use of pre-gelatined starch and cassava (70:30) bagasse flour, cassava starch and amaranth flour, in the proportion of 10:60:30, allowed the creation of instant pasta with a 3min boiling time, 101,46% mass increase and 0,6% loss of solids in boiling water, besides good physical, chem-ical and technological texture conditions, with 9,37 g (100 g)-1 of fibers, 10,41 g (100 g)-1 of proteins, 4449,09 gf of firmness and a low stickness of 324,19 gf, allowing the use of indus-trial waste on human food and a bigger range of healthy gluten-free products.